Targeted panel sequencing in pediatric primary cardiomyopathy supports a critical role of TNNI3. Issue 6 (22nd October 2019) - Kühnisch, Jirko; Herbst, Christopher; Al‐Wakeel‐Marquard, Nadya; Dartsch, Josephine; Holtgrewe, Manuel; Baban, Anwar; Mearini, Giulia; Hardt, Juliane; Kolokotronis, Konstantinos; Gerull, Brenda; Carrier, Lucie; Beule, Dieter; et al.
Abstract: The underlying genetic mechanisms and early pathological events of children with primary cardiomyopathy (CMP) are insufficiently characterized. In this study, we aimed to characterize the mutational spectrum of primary CMP in a large cohort of patients ≤18 years referred to a tertiary center. Eighty unrelated index patients with pediatric primary CMP underwent genetic testing with a panel‐based next‐generation sequencing approach of 89 genes. At least one pathogenic or probably pathogenic variant was identified in 30/80 (38%) index patients. In all CMP subgroups, patients carried most frequently variants of interest in sarcomere genes suggesting them as a major contributor in pediatric primary CMP. In MYH7, MYBPC3, and TNNI3, we identified 18 pathogenic/probably pathogenic variants ( MYH7 n = 7, MYBPC3 n = 6, TNNI3 n = 5, including one homozygous ( TNNI3 c.24+2T>A) truncating variant. Protein and transcript level analysis on heart biopsies from individuals with homozygous mutation of TNNI3 revealed that the TNNI3 protein is absent and associated with upregulation of the fetal isoform TNNI1. The present study further supports the clinical importance of sarcomeric mutation—not only in adult—but also in pediatric primary CMP. TNNI3 is the third most important disease gene in this cohort and complete loss of TNNI3 leads to severe pediatric CMP. Abstract :